2013
DOI: 10.1097/eja.0b013e32835f9a3b
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic neuropathic pain of different causes with the combination of oral methadone along with ketamine

Abstract: Editor,A recent discussion amongst us to improve the methods of scheduling operations led us to re-analyse the original data presented in the recent model. 1 This revealed small errors in four of the 153 data points published in our article. These were due to incorrectly labelled scheduled surgical list times (i.e. a half-day list mislabelled as full day and vice versa; two errors) and incorrectly applied gap 0265-0215 ß Re-plot of Fig. 4a of the original article: the degree of over-run (or under-run, negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Oral ketamine has been prescribed fairly commonly for home use in patients with chronic pain, following guidelines for dosing, 19 safety, and efficacy. 20,21 However, such data are not yet available in the setting of MDD.…”
mentioning
confidence: 99%
“…Oral ketamine has been prescribed fairly commonly for home use in patients with chronic pain, following guidelines for dosing, 19 safety, and efficacy. 20,21 However, such data are not yet available in the setting of MDD.…”
mentioning
confidence: 99%
“…Despite these similarities, the drugs present the following different selectivity: methadone presents a higher affinity for the opioid receptor (activator), while ketamine presents a higher affinity for the NMDA receptor (inhibitor) (6,9). It is well known that these systems present a synergistic effect, eliciting a better and safer analgesic effect even in patients with pain refractory to analgesics (16,(22)(23)(24). Ketamine is an arylcyclohexylamine derivative, with dissociative, analgesic, and anesthetic properties, due to several mechanisms, mainly the blockade of the NMDA receptor and activation of the opioid system.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these therapeutic limitations and to increase analgesic efficacy, multimodal analgesia (drug combination therapy) has been successfully used in pain therapy (15). In our previous report, we demonstrated that oral methadone plus ketamine was efficient to treat refractory neuropathic pain, reducing pain and decreasing several side effects (16).…”
Section: Randomization and Maskingmentioning
confidence: 97%
“…Combination of methadone with tricyclic antidepressants (Banks et al, 2010;Schreiber et al, 2014), methylph enidate (Schreiber et a l., 2017), delta9tetrahydrocannabinol (Cichewicz et al, 1999) and ketamine (Pelissier et al, 2003) have already been reported, but almost in acute preclinical pain models. Methadone/ketamine (de Godoy et al, 2013) and methadone/ibuprofen (Ferrer-Brechner and Ganz, 1984) combinations have been used as antinociceptive agents in the clinic, but controlled studies reported that ketamine alone is more effective than the methadone/ketamine combination (Rigo et al, 2017) and that at the long-term nonsteroidal anti-inflammatory drugs (NSAIDs) can result in increased risk of gastrointestinal and cardiovascular side-effects (Wehling, 2014;Ho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%